Operational Planning Implementation at Imported Beef Supplier Startup Meat Tech - Handoko, Tri; Syah, Tantri Yanuar Rahmat; Kustiawan, Unggul; Nofierni, Nofierni (INOVASI, 2025)
The main objective of this study is to highlight the operations and management of the beef industry in meat tech. PT Meat Tech is poised to become a leading provider of high-quality beef in the mid-range Horeca (Hotels, Restaurants, and Catering) sector within the Greater Jakarta area. By prioritizing quality and sustainability, PT Meat Tech ensures that all products are sourced from trusted suppliers, halal-certified, and safe for consumption. This commitment guarantees that customers receive beef that meets stringent food safety and taste standards, essential for the success of any culinary business. Middle-class Horeca in large metropolitan cities such as Jakarta, Bogor, Depok, Tangerang, and Bekasi are concerned with the quality of products and services offered by suppliers. PT Meat Tech as an imported beef supplier is concerned with these customer needs to increase consumer satisfaction. However, to create good product and service quality, companies need to manage their resources such as operational management, human resources, marketing, and finance. Business operation design consists of the preparation of plans and activity arrangements that include notifications and procedures, work flow and management resources to achieve PT Meat Tech's goals. PT Meat Tech emphasizes the implementation of product diversification strategies, distribution services, and online business models. Based on the strategy at the business level, namely the focus of product development strategies and product differentiation. Process technology integrated with business strategy will create inventory management, supply chain, logistics, and management information systems.